Deficit of PKHD1L1 in the dentate gyrus increases seizure susceptibility in mice. Issue 3 (6th September 2022) - Yu, Jiangning; Wang, Guoxiang; Chen, Zhiyun; Wan, Li; Zhou, Jing; Cai, Jingyi; Liu, Xu; Wang, Yun
Abstract: Epilepsy is a chronic neurological disorder featuring recurrent, unprovoked seizures, which affect more than 65 million people worldwide. Here, we discover that the PKHD1L1, which is encoded by polycystic kidney and hepatic disease1-like 1 ( Pkhd1l1 ), wildly distributes in neurons in the central nervous system (CNS) of mice. Disruption of PKHD1L1 in the dentate gyrus region of the hippocampus leads to increased susceptibility to pentylenetetrazol-induced seizures in mice. The disturbance of PKHD1L1 leads to the overactivation of the mitogen-activated protein kinase (MAPK)/extracellular regulated kinase (ERK)-Calpain pathway, which is accompanied by remarkable degradation of cytoplasmic potassium chloride co-transporter 2 (KCC2) level together with the impaired expression and function of membrane KCC2. However, the reduction of membrane KCC2 is associated with the damaged inhibitory ability of the vital GABA receptors, which ultimately leads to the significantly increased susceptibility to epileptic seizures. Our data, thus, indicate for the first time that Pkhd1l1, a newly discovered polycystic kidney disease (PKD) association gene, is required in neurons to maintain neuronal excitability by regulation of KCC2 expression in CNS. A new mechanism of the clinical association between genetic PKD and seizures has been built, which could be a potential therapeutic target for treating PKD-related seizures.